EPEN-15. Radiotherapy with helium ions has the potential to improve both endocrine and neurocognitive outcome in pediatric patients with ependymoma. (3rd June 2022) - Wickert, Ricarda; Adeberg, Sebastian; Deng, Maximilian; Tessonnier, Thomas; Hoeltgen, Line; Debus, Jürgen; Herfarth, Klaus; Harrabi, Semi
Abstract: BACKGROUND: Ependymoma are the third most frequent pediatric brain tumors. To prevent local recurrence, the resection site should be irradiated. Especially the treatment of pediatric patients requires precise dose application and optimal protection of organs at risk. Compared to photon radiation treatment, proton therapy often achieves better results regarding target coverage and organ-sparing. Due to their physical properties, helium ions can further reduce side effects, providing better protection of healthy tissue despite similar target coverage. PATIENTS AND METHODS: In our in-silico study, 15 pediatric patients (median age six years) with ependymoma located in the posterior cranial fossa were considered. All patients underwent adjuvant radiotherapeutic treatment with active scanned protons at Heidelberg Ion-Beam Therapy Center (HIT). Both helium ion and highly conformal IMRT plans were calculated to evaluate the potential dosimetric (and clinical) benefit of ion beam therapy compared to the current state of the art photon-based treatments. RESULTS: Target coverage was comparable in all three modalities (He, H +, Ph): homogeneity indices (HI) and inhomogeneity coefficients (IC) of HIHe =5.8±3.8, HIH + =7.5±4.0, HIPh =6.4±4.3, ICHe =0.2±0.1, ICH+ =0.2±0.1, ICPh =0.2±0.1. As expected, the integral dose absorbed by the healthy brain tissue could be reduced significantly using helium ions versus IMRT (-45.3%±15.1%). Based on our preliminary results, even compared to active scanned protons – currently the most precise radiation technique worldwide – the relative dose reduction for critical neuronal structures using helium ions on average amounts to -27.2%±14.4%. CONCLUSION: Previous studies could clearly demonstrate that the dosimetric advantage of protons translates into a measurable clinical benefit for pediatric patients with brain tumors. Given the dose response relationship of critical organs at risk, the results of our in-silico study provide a strong rationale that the use of helium ions has the potential to even further reduce the risk for treatment related sequelae.